Agency Costs and Export Activity among Family Businesses - Wyrobek, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The purpose of this publication is to investigate the relationship between concerns about external and internal agency conflicts in family businesses and family control over the company and forms of international cooperation. The study is based on surveys conducted among 101 family businesses in Poland. The author examines the following theses in particular: ‒ the high level of concern about internal agency conflicts (within the company) implies that there will be more family control over the business; ‒ some forms of international cooperation are rarely used by family businesses due to concerns about international (external) agency conflicts that may arise between a family business and its foreign partners; ‒ the main reason for undertaking international cooperation is to increase sales and reduce operating costs.